Luigi Nono und der Osten - Wertenson, Birgit Johanna; Storch, Christian 1979- (Mainz Are Musik, 2016)
This publication 'Luigi Nono und der Osten' explores the person and work of the Italian composer against the backdrop of an 'East' that is not only to be understood as a geographical direction, but also includes countries with a communist or socialist character. As a member of the Italian Communist Party, Nono (1924-1990) not only bore political witness with his works, but also took on the role of an enlightener and mediator between 'East' and 'West' throughout his life through his writings, events and travels. The analysis and contextualisation of these roles are the subject of the book, which works largely with source material, particularly from the Archivio Luigi Nono: with documents on his travels, from Buenos Aires to Moscow, his acquaintances, correspondence, speeches and activities. In their contributions, the authors explore the mutual influence between Nono and the avant-garde movements in countries beyond the Iron Curtain, the development of Nono's reception there, his work in favour of socialist ideas in Latin America and Europe as well as the background to cultural-political resistance and scandal - and, last but not least, they explore the central and difficult question of defining and evaluating Luigi Nono's understanding of communism.
Keywords: Nono, Luigi -- 1924-1990; Music history; Politics